2018
DOI: 10.1002/14651858.cd012543.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Activity monitors for increasing physical activity in adult stroke survivors

Abstract: Only four small RCTs with 274 participants (three in inpatient rehabilitation and one in the community) have examined the efficacy of activity monitors for increasing physical activity after stroke. Although these studies showed activity monitors could be incorporated into practice, there is currently not enough evidence to support the use of activity monitors to increase physical activity after stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 64 publications
0
45
0
1
Order By: Relevance
“…Virtual reality video games, activity monitors, and handheld computer devices are accessible, affordable, and enjoyable [8], and together can provide a digitally enabled rehabilitation environment by providing more opportunity and greater motivation to increase taskspecific practice in hospital [9] and in the home setting [10]. However, evidence of their impact on outcomes is limited and focused on stroke rehabilitation [11,12]. A systematic review of virtual reality interventions in people after stroke (72 studies) demonstrated a moderate effect on balance, but no effect on walking speed or global motor function when delivered as an adjunct to usual rehabilitation [11].…”
Section: Introductionmentioning
confidence: 99%
“…Virtual reality video games, activity monitors, and handheld computer devices are accessible, affordable, and enjoyable [8], and together can provide a digitally enabled rehabilitation environment by providing more opportunity and greater motivation to increase taskspecific practice in hospital [9] and in the home setting [10]. However, evidence of their impact on outcomes is limited and focused on stroke rehabilitation [11,12]. A systematic review of virtual reality interventions in people after stroke (72 studies) demonstrated a moderate effect on balance, but no effect on walking speed or global motor function when delivered as an adjunct to usual rehabilitation [11].…”
Section: Introductionmentioning
confidence: 99%
“…During rehabilitation after a stroke, patients require the input of several skilled health care personnel, including rehabilitation physicians, physiotherapists, speech therapists, and occupational therapists but these resources are often unavailable, impeding the recovery from physical limitations among stroke survivors. Thus, technology in home-base rehabilitation is generally considered a positive factor for hospitals and the community, economically and logistically, and, when integrated with conventional rehabilitation protocols, increases activities that are vital for reducing stroke-related disabilities, 20 given that after a stroke, even if mild, patients experience reduced physical activity.…”
Section: Introductionmentioning
confidence: 99%
“…Technologic advancement and improvement in step counter development could help clinicians to obtain new and more reliable data on real-life patients' mobility [14].…”
Section: Introductionmentioning
confidence: 99%
“…Step counters can be used to detect post-stroke patients' activity levels [25][26][27], assess gait and balance parameters [28,29], and guide the patients in performing exercises [30], as well as acting as a stimulus to increase in-and out-patient activity levels [14]. The literature shows that the monitoring of patients' mobility in an inpatient setting can give information similar to advanced and time-consuming techniques, such as behavioral mapping, and it can be useful to collect the activity levels of hospitalized patients [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation